Investigating the effect of health literacy level on improving the quality of care during pregnancy in pregnant women covered by health centers - Leila Asadi; Fatemeh Amiri; Hadise Safinejad (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Health literacy is the capacity to acquire, process, and understand basic information and services necessary for appropriate health decisions. Given the importance of health literacy in women, the aim of the present study was to determine the effect of health literacy level on improving the quality of care during pregnancy in pregnant women. MATERIALS AND METHODS: The present study was a cross-sectional analytical study. In this study, 130 women referred to Yazd health centers were examined. Health literacy questionnaires and a researcher-made checklist of the quality of pregnancy care were used to gather information. The researcher-made checklist of the quality of pregnancy care was in accordance with the standard protocol of the Ministry of Health and Medical Education, entitled Integrated Health Care for Pregnant Mothers, which was validated and reliable. SPSS statistical software version 19 and t-test and ANOVA statistical tests were used to analyze the data. RESULTS: According to the findings, the average score of health literacy in pregnant women was 74.09, which showed that the level of health literacy was in the marginal or border range. People with higher health literacy received significantly more prenatal counseling than other women and had a planned pregnancy (P = 0.04). CONCLUSION: The level of health literacy in pregnant women is unfavorable. Given that the high level of health literacy in women in society can lead to an increase in the quality of pregnancy care, so to increase health literacy in women, it is recommended that regular training in society by health-care providers be given more attention.